A Treatise on Commerce Written in Eastern Turki: Risâle-i Sevdâgerçilik - Fatih Erbay (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
The Chagatai literary language entered a new era with the 19th and 20th centuries, when Turks living in the Tarim Basin were particularly active producing works in the writing tradition of Chagatai Turkish. Numerous Eastern Turki works of this era were brought to the West by Swedish missionaries. Jarring bought the commerce treatise discussed in this study from Roze Akhon, a book peddler in Kashgar, and it was donated to Lund University in Sweden in 1982 and registered under the Jarring Collection (Jarring Prov. 397). The 94-page treatise explains occupational subtleties from a general Islamic perspective. Certain features of Risâle-i Sevdâgerçilik [Treatise on Commerce] are in line with the futuwwatnamas [rules and regulations of Turkish-Islamic guilds] written in Anatolia. These similarities in both style and content are remarkable. Although no date is found on the manuscript, when considering the catalog record and the language of the work, it can be said to have been written in the early 20th century. This article aims to introduce Risâle-i Sevdâgerçilik, which was written in Eastern Turki and to provide information about its contents in this context. The study goes on to state the salient points of the phonetic features detected in the work through examples. The work classifies and analyzes the examples on suffix incompatibility in the text under two headings: suffix incompatibility in Turkish words and suffix incompatibility in loanwords.